Factors Influencing Income Smoothing Practices With Firm Size Moderation - Henryanto Wijaya, Mauren, Hadi Cahyadi (Jurnal Akuntansi, 2020)
The purpose of this study is to determine the effect of profitability, financial leverage, and dividend policy on income smoothing in manufacturing companies registered on the Indonesia Stock Exchange in 2016-2018 with firm size as a moderating variable. This study used 38 manufacturing companies as a sample in this study and analysis of logistic regression. The results of this study indicated that profitability has a significant negative effect on income smoothing; firm size has a significant positive effect on income smoothing. In contrast, financial leverage and dividend policy have an insignificant effect on income smoothing. Firm size weakens profitability and the effect of dividend policy on income smoothing while firm size does not moderate financial leverage's effect on income smoothing.